Prime ministers in the age of austerity: an increase in the personalisation of voting behaviour - Lobo, Marina Costa (2018)
This article tests the personalisation thesis in Portugal (2002–2015), as well as its causes, focusing on changes in the level of party identification and perceptions of the economy. Portugal is an interesting example given its recent experience of a harsh economic crisis, as well as a decline in party identification. Results confirm a growing exogenous impact of leader evaluations on voting over the period but not in a linear fashion. During the crisis, the growing trend of leader effects for the incumbent party continues for those voters who have a positive perception of the economy. Conversely, for the main opposition party, leader effects are greater for those who perceive the economy as being worse. Thus the crisis operates as a catalyst for leader effects. The impact of leaders is also greater among the de-aligned, the numbers of which rise considerably during the period under analysis. It is voters with no party identification, who use leaders as proxies to a greater extent. These conclusions may extend to further studies on leader effects in Western democracies and help to shed light on the process through which leaders are becoming more relevant in voting decisions.